Two neutrophilic dermatoses captured simultaneously on histology - Christina Wlodek; Nidhi Bhatt; Cameron Kennedy (Dermatology Practical & Conceptual, 2016)
A number of neutrophilic dermatoses are associated with malignancies and their treatment. These rarely occur together in the same patient.